In Vitro Cytotoxic and Leishmanicidal Activity of Isolated and Semisynthetic ent-Pimaranes from Aldama arenaria - de Oliveira, Adriana da Silva Santos; Conrado, Gabrielly Galdino; Grazzia, Nathalia; Miguel, Danilo Ciccone; Franchi Júnior, Gilberto Carlos; Garcia, Vera Lúcia (Planta Medica, 2022)
Two pimaranes ent-pimara-8(14),15-dien-19-oic acid (1) and ent-8(14),15-pimaradien-3β-ol (2), isolated from Aldama arenaria, and six semi-synthetic derivatives methyl ester of the ent-pimara-8(14),15-dien-19-oic acid (3), ent-pimara-8(14),15-dien-19-ol (4), acetate of ent-pimara-8(14),15-dien-19-ol (5), ent-pimara-8(14),15-dien-19-ol succinic acid (6), acetate of ent-8(14),15-pimaradien-3β-ol (7), ent-8(14),15-pimaradien-3β-ol succinic acid (8) were evaluated in vitro for their cytotoxic activities to childhood leukemia cell lines and leishmanicidal activity against the parasite Leishmania amazonensis. Among these compounds, 1 to 6 presented moderate cytotoxic activity, with compound 4 being the most active (GI50 of 2.6 µM for the HL60 line) and the derivatives 7 and 8 being inactive. Against the parasite Leishmania amazonensis, the most promising derivative was the acetate of ent-pimara-8(14),15-dien-19-ol (5), with EC50 of 20.1 µM, selectivity index of 14.5, and significant reduction in the parasite load. Pimarane analogues 1, ent-pimara-8(14),15-dien-19-oic acid, and 2, ent-8(14),15-pimaradien-3β-ol, presented different activities, corroborating the application of such molecules as prototypes for the design of other derivatives that have greater cytotoxic or leishmanicidal potential.
Keywords: leishmanicidal activity; cytotoxic activity; Leishmania amazonensis; pimaranes; Aldama arenaria (syn. Viguiera arenaria); Asteraceae